2017
DOI: 10.1038/s41598-017-14832-9
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of OsNramp5 using the CRISPR/Cas9 system produces low Cd-accumulating indica rice without compromising yield

Abstract: Rice grain with excessive cadmium (Cd) is a major source of dietary Cd intake and a serious threat to health for people who consume rice as a staple food. The development of elite rice cultivars with consistently low Cd content is challenging for conventional breeding approaches, and new strategies urgently need to be developed. Here, we report the development of new indica rice lines with low Cd accumulation and no transgenes by knocking out the metal transporter gene OsNramp5 using CRISPR/Cas9 system. Hydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
204
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 434 publications
(207 citation statements)
references
References 54 publications
2
204
1
Order By: Relevance
“…For instance, using the CRISPR/Cas9 to introduce a loss‐of‐function mutation into the Waxy gene reduced the amylose content and generated new glutinous rice (Zhang et al ). Knocking out the metal transporter gene OsNramp5 using CRISPR/Cas9 system produces low Cd‐accumulating indica rice without compromising yield (Tang et al ). CRISPR/CAS9‐mediated editing of the fragrant gene BADH2 in rice reduced the Badh2 RNA level and increased 2‐acetyl‐1‐pyrroline content in the mutant (Shao et al ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, using the CRISPR/Cas9 to introduce a loss‐of‐function mutation into the Waxy gene reduced the amylose content and generated new glutinous rice (Zhang et al ). Knocking out the metal transporter gene OsNramp5 using CRISPR/Cas9 system produces low Cd‐accumulating indica rice without compromising yield (Tang et al ). CRISPR/CAS9‐mediated editing of the fragrant gene BADH2 in rice reduced the Badh2 RNA level and increased 2‐acetyl‐1‐pyrroline content in the mutant (Shao et al ).…”
Section: Resultsmentioning
confidence: 99%
“…There are several biotechnological approaches to decrease Cd in rice grain. Knockout of OsNRAMP5, a major transporter for Mn and Cd uptake in rice, could produce very low Cd‐accumulating rice (Sasaki et al 2012; Tang et al 2017). However, OsNRAMP5 knockout plants have a potential risk of Mn deficiency under low Mn supply conditions because of shortages of Mn uptake (Sasaki et al 2012; Yang et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Off-target mutation is a common and critical problem associated with CRISPR/Cas9-mediated genome editing in human cells, but it has rarely been reported in gene-edited plants. Several studies have reported that there was no offtarget mutation, not only in Arabidopsis, but also various crop species Pan et al, 2016;Braatz et al, 2017;Jia et al, 2017;Tang et al, 2017;Cai et al, 2018). We analyzed the potential off-target mutagenesis on loci highly similar to the target sequence.…”
Section: Discussionmentioning
confidence: 99%